PENGARUH STRATEGI BRAND EXTENSION TERHADAP MINAT BELI KONSUMEN (Studi Kasus PT.Bank Negara Indonesia Syariah cabang Pekanbaru - Marlina, Yeni; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Brand extensionstrategyis the use ofa brandthat has been establishedfor theenteringclass ofnewproductsaimed at providingdirection tothe efforts ofthe companyfromtime to timeis gettingbetter, at all levelsand referenceas well asits locationin abrand extensionthatseen with theexpansion ofthe product onPT.BankPekanbarubranch of the Indonesianstate. Buying interestcustomers grewbecausetheirmotivesbased onattributesin accordancewith the wishesand needsin using or purchasingthe expansion ofthe product, based onthese twocompaniesshould beappropriateto design a strategyof brandextensiontoattractbuying interestfromconsumers themselvesto beinterested in theexpansion ofthe products offeredso that ifconsumers have beeninterested in theexpansion of theproduct and servicesofferedso thatif consumershavean interest inthose productsthenthere will be adecision tobuy the product.This research was conducted in the State Indonesia SyariahPT.BankPekanbaru branch located in the Sudirman No. 484, Pekanbaru. The purpose of this study was conducted to determine the effect of brand extension strategy towards customer buying interest on the State PT.Bank Indonesia Pekanbaru branch. In this researchmethodologyis descriptiveandquantitativewithSPSS, where sampleswere used thatcustomers of BankNegara IndonesiaSyariahPekanbarubranchandas a sourceof informationistheproductmanagersection.Todetermine the sampleusing the formulaSlovin, samplingwithpurposivesamplingmethod.The technique of collectingdata throughinterviews, observationandquestionnaires.From theresults of data analysisincludevalidity,reliability, andsimple linear regression, the strategy of brand extensionin this study includefourcomponents of boththeknowledge ofthe brand(brandknowledge), perceived quality(perceived quality), innovativeness(innovative), the consistency ofthe brand concept(brandconceptconsistency).Each hasindicatorinterrelatedandpositivestrivingtowardscustomersbuying interestonPT.BankPekanbaruCountryIndonesiaSyariahbranch.Keywords: Brand Extension Strategy, Interests Buy Customer